Effectiveness of sugar sweetened beverages tax on health and healthcare costs: a systematic review - Diana Safraa Selimin,; Nazarudin Safian,; Mohd Rohaizat Hassan,; Mohd Rizal Abdul Manaf,; Qistina Mohd Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Taxing sugar-sweetened beverages (SSB) is one of many other best strategies to reduce consumption of SSB among populations. It is known that SSB consumption is the main contributor which cause obesity and further lead to non-communicable diseases. This study aimed to gather the evidence on the effectiveness of sugar-sweetened beverages tax implementation, in terms of health outcome and healthcare cost benefit. A systematic review was done related to literature that reported about effectiveness of sugar-sweetened beverages tax implementation, in terms of health outcome and healthcare cost benefit. Four databases were used to identify the literature, namely PubMed, Cochrane, Scopus and Ovid and Medline. PRISMA flow checklist was used as a guide to search for the eligible articles. In total, there were sixteen eligible articles included in this systematic review. All studies are simulation studies. Results showed that both excise and ad valorem tax are effective to reduce healthcare costs and could avert diseases related to high sugar intake. Other than that, it is proven that implementing tax will gain favorable health outcome rather than do nothing. Better results seen when the tax is increased. As a conclusion, SSB tax is proven as an effective public health intervention in terms of giving benefit to the health outcome and healthcare cost.